PENGARUH LITERASI KEUANGAN, PENGELOLAAN KEUANGAN, DAN PAYMENT GATEWAY, TERHADAP KINERJA PELAKU UMKM (STUDI PADA PELAKU UMKM DI PKOR WAY HALIM KOTA BANDAR LAMPUNG) - Dianti, Auliyah Nuraini; Wardianto, Kussuyatmono Bagus; Harori, Muhammad Iqbal (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
With the increasing role of MSMEs in the local economy, a good understanding of financial literacy and management, as well as the adoption of efficient payment technology are key to improving business performance.”This study aims to analyze the influence of financial literacy, financial management, and payment gateway use on the performance of MSME actors in PKOR Way Halim, Bandar Lampung City. The method used in this study is a survey with an associative quantitative approach. Data was collected through interviews and questionnaire distribution using the judgemental sampling technique, which involved 100 respondents of MSME actors at PKOR Way Halim. The data analysis technique in this study is multiple linear regression analysis using the SPSS Version 30 program. The results of the study show that financial literacy and payment gateways have a positive and significant effect on the performance of MSMEs, while financial management does not show a significant influence on the performance of MSMEs in PKOR Way Halim”